Continuing Challenges in Advancing Preclinical Science in Skeletal Cell‐Based Therapies and Tissue Regeneration. (4th September 2018) - Featherall, Joseph; Robey, Pamela G; Rowe, David W
ABSTRACT: Cell‐based therapies hold much promise for musculoskeletal medicine; however, this rapidly growing field faces a number of challenges. Few of these therapies have proven clinical benefit, and an insufficient regulatory environment has allowed for widespread clinical implementation without sufficient evidence of efficacy. The technical and biological complexity of cell‐based therapies has contributed to difficulties with reproducibility and mechanistic clarity. In order to aid in addressing these challenges, we aim to clarify the key issues in the preclinical cell therapy field, and to provide a conceptual framework for advancing the state of the science. Broadly, these suggestions relate to: (i) delineating cell‐therapy types and moving away from "catch‐all" terms such as "stem cell" therapies; (ii) clarifying descriptions of cells and their processing; and (iii) increasing the standard of in vivo evaluation of cell‐based therapy experiments to determining cell fates. Further, we provide an overview of methods for experimental evaluation, data sharing, and professional society participation that would be instrumental in advancing this field. © 2018 American Society for Bone and Mineral Research.